Strategic management of people and organizational commitment in hospital organizations - Silva, Claudio Cesar; Leite, Nildes Raimunda Pitombo; Rodrigues, Leonel Cezar (Revista de Administração da UFSM, 2016)
This research is characterized as a qualitative approach based on multiple-case studies in hospital organizations. These findings enhance our understanding of how the strategic management of people can foster organizational commitment, using managers of hospital organizations as subjects, and expanding discussions about the concept of organizational commitment. Data were collected using in-depth interviews, qualitative survey questionnaires and documentary research. Data management and analysis were performed using analysis strategies, reflective analysis, document analysis and, consequently, triangulation of data. Overall, these results show that when the policies and practices of strategic management of people are integrated into organizational strategies, there is a tendency of people management act more focused on commitment model. Moreover, the central aspects of the concepts and perceptions about organizational commitment drawn up by managers highlight the commitment, dedication and identification with the organization as affective dimension characteristics of commitment found in the literature. However, no references were found to normative and instrumental dimensions.